2014
DOI: 10.2134/agronj14.0200
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Maize Phenology: Intercomparison of Functions for Developmental Response to Temperature

Abstract: Accurate prediction of phenological development in maize (Zea mays L.) is fundamental to determining crop adaptation and yield potential. A number of thermal functions are used in crop models, but their relative precision in predicting maize development has not been quantified. The objectives of this study were (i) to evaluate the precision of eight thermal functions, (ii) to assess the effects of source data on the ability to differentiate among thermal functions, and (iii) to attribute the precision of therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 34 publications
(69 reference statements)
6
93
0
4
Order By: Relevance
“…Our approach allows accurate derivation of parameters for wheat phenology models, but for maize the approach has more limitations. This could be due to a more complex phenological response to temperature in maize (Kumudini et al ., ), oversimplistic assumptions about the development phase that is sensitive to photoperiod (Birch et al ., ), as well as to overestimation of the effect of photoperiod in tropical regions where the longest and shortest days are not very different (see equation and Table ). These limitations for maize need to be considered when employing our approach, and we suggest that the thermal model is used for maize.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach allows accurate derivation of parameters for wheat phenology models, but for maize the approach has more limitations. This could be due to a more complex phenological response to temperature in maize (Kumudini et al ., ), oversimplistic assumptions about the development phase that is sensitive to photoperiod (Birch et al ., ), as well as to overestimation of the effect of photoperiod in tropical regions where the longest and shortest days are not very different (see equation and Table ). These limitations for maize need to be considered when employing our approach, and we suggest that the thermal model is used for maize.…”
Section: Discussionmentioning
confidence: 99%
“…However, this assumption can often be violated as shown in several maize model intercomparison studies (e.g., [19,20]). Following our experience with tuning APSIM simulations for rainfed maize in the US Midwest [8], we tested multiple modifications throughout the simulation pipeline.…”
Section: Multiple Avenues To Improve Performancementioning
confidence: 99%
“…The degree of climate change impact on sugarcane is associated with geographic location and adaptive capacity. However, there has been little research conducted to document these effects as found by Kumudini et al (2014). Based on pot and field studies with intensive measurements of physiological, growth, and yield traits, we also found that some sugarcane genotypes are more tolerant to stress environment than others (Zhao et al 2015).…”
Section: Introductionmentioning
confidence: 97%